Rainbow Vectors for Broad-Range Bacterial Fluorescence Labeling. - Mariette Barbier; F Heath Damron (PLoS ONE)
Since their discovery, fluorescent proteins have been widely used to study protein function, localization or interaction, promoter activity and regulation, drug discovery or for non-invasive imaging. They have been extensively modified to improve brightness, stability, and oligomerization state. However, only a few studies have focused on understanding the dynamics of fluorescent proteins expression in bacteria. In this work, we developed a set plasmids encoding 12 fluorescent proteins for bacterial labeling to facilitate the study of pathogen-host interactions. These broad-spectrum plasmids can be used with a wide variety of Gram-negative microorganisms including Escherichia coli, Pseudomonas aeruginosa, Burkholderia cepacia, Bordetella bronchiseptica, Shigella flexneri or Klebsiella pneumoniae. For comparison, fluorescent protein expression and physical characteristics in Escherichia coli were analyzed using fluorescence microscopy, flow cytometry and in vivo imaging. Fluorescent proteins derived from the Aequorea Victoria family showed high photobleaching, while proteins form the Discosoma sp. and the Fungia coccina family were more photostable for microscopy applications. Only E2-Crimson, mCherry and mKeima were successfully detected for in vivo applications. Overall, E2-Crimson was the fastest maturing protein tested in E. coli with the best overall performance in the study parameters. This study provides a unified comparison and comprehensive characterization of fluorescent protein photostability, maturation and toxicity, and offers general recommendations on the optimal fluorescent proteins for in vitro and in vivo applications.